تحديد العوامل التصميمية لخنادق الأكسدة في معالجة مياه الصرف الصحي للتجمعات السكانية الصغيرة في الساحل السوري. - سلمان, هناء; جناد, هيثم; قاسم, صفاء (Latakia University Journal -Engineering Sciences Series, 2019)
درست العوامل التصميمية لخنادق الأكسدة لتحقيق أفضل كفاءة في إزالة الملوثات العضوية والمواد العالقة والمغذيات ( الفوسفور والنتروجين ) باستخدام نموذج مخبري ومياه صرف حقيقية لقرية الحارة – مدينة اللاذقية. أجريت التجارب في عام2011, وتم تشغيل النموذج بمدد بقاء هيدروليكية من 8 h إلى ,32 h وبمجال F/M (0.033– 0.158 ), وقيم MLSS mg/l( 2000 – 3800 ), وبدرجات حرارة C0( 9.3 – 26.5 ), قيم الـpH هي( 7.5 – 8.44 ), أما قيم الأوكسجين المنحل( DO ) في الحوض بعد نهاية التهوية فهي mg/l (0.4 – 6.9) , نسبة إعادة الحمأة هي 100%, عمر الحمأة ( 29-20 ). متوسط حمولة التلوث بالـ BOD5 في اليوم 149 mg/l شتاءً و 387.16 mg/lصيفاً, القيمة الوسطية الداخلة من الـTN و الـ TP خلال مرحلة الدراسة هي 10.75 mg/l و8.6 mg/l على التتالي. مدة البقاء الهيدروليكية الأنسب للتشغيل في الحالة الديناميكية هي 14 ساعة في فصل الشتاء و( 18-24 ) ساعة في فصل الصيف. تحققت نسبة إزالة عند مدة بقاء هيدروليكية 24 h لـ BOD5 , COD , TSS, TP هي: ,91.4 % %91.25 , %92.34 , 18.91 % على التتالي, ولم تحدث إزالة للنتروجين في الحوض, وكانت T C0=25.5 C° و 7.63= pH و F/M = 0.09 وDO =2.5 mg/l . تحققت إزالة النتروجين الكلي والفوسفور الكلي بتوفير منطقة anoxic في التشغيل الديناميكي: 59% و 37.8% على التتالي. زمن تكثيف الحمأة الناتجة 45 min وعامل المقاومة النوعية على الترشيح لها r`= 362.8 * 1010 cm/gr ومن ثم هي حمأة سهلة التكثيف والترشيح, وقيمة SVI = 42.37 ml/g مما يدل على أن الحمأة سهلة التكثيف والترشيح وأنَ مياه الصرف القادمة لا تحتوي مخلفات صناعية. Studying design parameters of oxidation ditches was done to achieve the best removal efficiency of organic pollutants, suspended solids, and nutrition elements (Nitrogen and Phosphorous) using a pilot at Wastewater treatment plant in AL-HARAH village– LATTAKIA City. The experiments were done in 2011. The pilot was operated with different hydraulic retention times from 8h to 32 h, F/M (0.033 – 0.132), MLSS( 2000 – 3800 ) mg/l, TC0 ( 9.3 – 26.5 ), pH( 7.5 – 8.44 ), dissolved oxygen in basin and after the end of aeration ( 0.4–6.9 ) mg/l, and returned activated sludge was 100%, the solids retention time in the pilot is ( 20-29 ) d. At every hydraulic retention time DO, pH, TC0 were determined in basin, and the input and output of BOD5, COD, TSS, TN, TP. The characterization of input wastewater to the plant treatment was determined, the average of BOD5in in Winter was 149 mg/l, and the average in Summer was 387 mg/l. The average of TNin and TPin during the studying period were 10.75 mg/l and 8.6 mg/l consecutively. The suitable hydraulic retention time is (14) h in Winter, and ( 18 – 24 )h in Summer. The percentage removal of BOD5 , COD, TSS, TP at hydraulic retention time = 24h was 91.4%, 91.25%, 92.34%, 18.91% consecutively, and denitrification did not carry out, and DO was2.5mg/l, and T C0=25.5, F/M = 0.09, pH=7.63. Denitrification and Phosphorous removal were 59% and 37.8% consecutively with anoxic zone in dynamic operating. Production sludge had good characters with thickening time 45 min, specific resistance parameter on filtration 362.8*1010 cm/g, and SVI=42.37 ml/g.